Enhancing Green Purchase Intention Through Corporate Social Responsibility (CSR): The Mediating Role of Green Perceived Value - Zaneta Zakirena Sanjiwo; Nurdin Sobari (Indonesian Interdisciplinary Journal of Sharia Economics (IIJSE), 2025)
This study aims to analyze the role of green brand image, green trust, and green perceived value (GPV) as mediators between Corporate Social Responsibility (CSR) and consumer responses, including green purchase intention (GPI), word-of-mouth (WOM), and willingness to pay (WTP), in the context of developing and marketing environmentally friendly products in Indonesia's oil and gas industry. Data was collected through an online survey targeting consumers of oil and gas products, focusing on their perceptions of the benefits of environmentally friendly products and the company's CSR initiatives. The independent variable in this study is CSR, while the mediating variables include green brand image, green trust, and green perceived value. The dependent variables are green purchase intention (GPI), word-of-mouth (WOM), and willingness to pay (WTP). The data were analyzed using the Structural Equation Modeling (SEM) method to explore direct and indirect relationships among variables. The findings of this study are expected to help companies understand the factors influencing consumer behavior, enhance the adoption of environmentally friendly products, and support sustainability strategies in the energy sector.